Contribution of Multimedia to Girls' Experience of Citizen Science. (18th November 2016) - Flagg, Barbara N.
The mixed methods randomized experimental study assessed a model of engagement and education that examined the contribution of SciGirls multimedia to fifth grade girls' experience of citizen science. The treatment group (n = 49) experienced 2 hours of SciGirls videos and games at home followed by a 2.5 hour FrogWatch USA citizen science session. The control group (n = 49) experienced the citizen science session without prior exposure to SciGirls . Data from post surveys and interviews revealed that treatment girls, compared to control girls, demonstrated significantly greater interest in their FrogWatch USA session and significantly greater learning about the unique features of the practice of citizen science. Both treatment and control groups were moderately interested in finding out more about other citizen science projects and somewhat likely to look for another citizen science project to do in the future. Both groups displayed equal and high self-efficacy ratings with respect to their FrogWatch USA session and future citizen science projects. Within the treatment group, prior exposure to SciGirls multimedia produced a significantly stronger impact on minority girls than non-minority girls for interest and self-efficacy in citizen science. Treatment girls felt that SciGirls multimedia showed them the process and practice of citizen science, demonstrated the fun of citizen science, and presented peers with whom they could identify. Incorporating multimedia is recommended as an effective method for influencing girls' citizen science interest, self-efficacy and learning.